THE PROCESS OF FORMATION OF EARLY ARCHIVES - Khushmatova, S. (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the formation of early archives and their historical significance in state administration and the preservation of cultural heritage, addressing the lack of analysis regarding the political and cultural contexts that shaped early archival systems. Method: Employing a historical approach, the research examines primary and secondary sources from ancient civilizations such as Mesopotamia, Egypt, and Rome to understand how the processes of collecting, systematizing, and archiving documents evolved alongside political, technological, and social developments. Results: The findings reveal that archives played a crucial role in ensuring state stability through the documentation of legal codes, treaties, and property rights, as well as serving essential religious and cultural functions in ancient societies. These early archival systems were foundational in maintaining historical memory and facilitating public administration. Novelty: This study contributes to archival and historical scholarship by highlighting how ancient archival practices established the conceptual and functional basis for modern document management and cultural preservation, emphasizing their enduring relevance in the digital era.